PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN KOOPERATIVE TIPE JIGSAW - ., marliana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this study is to improve mastery of subject matter that has been studied and accepted by students. This study uses action research developed by Kemmis and Mc Taggert that use a cycle of two rounds. Each round consists of four stages, namely: design, activity and observation, reflection, and refining. The target of this study were 28th grade students of SD Negeri 1 Bayeun. The data obtained in the form of formative test results, observation sheets of teaching and learning activities by processing qualitative values. From the results of the analysis it was found that student learning outcomes experienced an increase from the first cycle of the formative test scores of 72.86 students to 81.79 in the second cycle and students' learning completeness in the first cycle which was 67.86% to 92.86% in the second cycle. The conclusion of this study is that the use of cooperative models of the jigsaw type can positively influence learning motivation, collaboration and increase the value of learning outcomes of fifth grade students at SD Negeri 1 Bayeun, and this learning model can be used as an alternative science or science learning.